Явище американської експериментальної прози в постмодерністській поетиці - Філоненко, 3. Л.; Filonenko, Z. L. (Волинський національний університет імені Лесі Українки, 2012)
Статтю присвячено дослідженню постмодерністської експериментальної прози з погляду постмодерністської поетики та розглянуто важливе значення цього новаторського явища для літературознавства. The article is devoted to the study of postmodern experimental prose and its main characteristic features. The notion of American postmodern experimental prose from the point of view of postmodern poetics has been determined. The importance of this innovative phenomenon for the development of literary studies is being given.
The Phenomenon of American Experimental Prose in Postmodern Poetics
Keywords: експериментальна проза; postmodern experimental prose; постмодерністська поетика; postmodern poetics; новаторство; innovation